THE INFLUENCE OF PROJECT CITIZEN LEARNING MODEL AND CITIZENSHIP COMPETENCE ON STUDENT PPKN LEARNING OUTCOMES AT SMP PAHLAWAN NASIONAL MEDAN - Fauziah Desrini; Deny Setiawan; Tappil Rambe (Jurnal Ilmiah Teunuleh, 2021)
This study aims to analyze: (1) the influence of Project Citizen learning model is higher compare to Conventional learning model; (2) PPKn learning outcomes of students who have higher nationality competencies compared to students who have low citizenship competencies (3) interactions between Project Citizen learning models and citizenship competencies in influencing student PPKn learning outcomes. Quasi Experimental Design research with factorial 2x2. The instruments used are PPKn learning results test and citizenship competency instrument. Data analysis using two-lane anava. The results showed: There is an influence of Project Citizen learning model on the learning outcomes of PPKn students in grade VII of SMP Pahlawan Nasional Medan. PPKn learning outcomes of students who have higher nationality competencies than students who have low citizenship competencies. There is an interaction between the learning model of Project Citizen and Citizenship Competency towards the learning outcomes of PPKn Students at Pahlwan National Junior High School Medan.